Popular Formulas in Sara Shepard's Pretty Little Liars - Pratiwi Wiranti; Rahmawan Jatmiko (Lexicon, 2018)
This study investigates the popular formulas found in Sara Shepard’s novel entitled Pretty Little Liars and examines how the popular formulas contributes to the success of the novel. In order to meet these objectives, this paper adopts the theory of popular genre and John G. Cawelti’s approach to popular formulas. This research is a library research where the primary data were obtained from the novel. Furthermore, other books related to popular formulas and online information from credible sources were also consulted. The results of the study show that the popular formulas in Pretty Little Liars include gothic romance, questioning sexuality, sibling rivalry, self-esteem issues, and forbidden love.